Fruit Bats: Their Importance, Threats and Conservation - Singh, Rajwinder (International Journal of Bio-resource and Stress Management, 2023)
Bats are nocturnal mammals which lives in large aggregations as colonies, hang their feet to twig of tree upward side, provide widespread ecological and monetary services via pollination, seed dispersal, rejuvenation of forests, guano as nutrient rich fertilizer and agricultural pest control. Different factors like exposure to heavy metals, pesticides, hunting, diminishing food supply, habitat destruction, forest fires and diseases are responsible for decreasing bat population, but urbanization greatly affects the composition and structure of inhabiting animal communities by transforming the natural habitats into environments dominated by human constructions. Micro bats feed on insect pests and help to reduce pesticide application in agricultural crops, whereas fruit bats feed on horticultural orchards like guava, ber and litchi thus act as pest. Bats are reservoirs of many pathogens like hendra, nipah, tioman, European lyssa and ebola viruses which cause several epidemic diseases among humans and domestic animals. Among 60 countries around the world, more than 200 bat species are considered to be threatened (critically endangered, endangered or vulnerable) by the International Union for the Conservation of Nature (IUCN). Using different eco-friendly methods like artificial lights and netting we can save our orchards and conserve fruit bats which will be helpful in the maintenance of ecological balance of nature.